PEMBINAAN TAHSINUL QIRA’AH UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN TK/TPA AL-MUHAJIRIN, DESA PATIONGI, KEC. PATIMPENG, KAB. BONE - Azizah Azizah; Muhammad Ikbal; Kusnadi (INKAMKU : Integrasi Akademisi dan Masyarakat yang Berkualitas, 2025)
The development of Kindergartens (TK) and Al-Qur'an Education Parks (TPA) is a strategic effort in shaping the character and religious knowledge of children from an early age. This development activity includes teaching to read the Qur'an, understanding morals, fiqh, and Islamic history with fun interactive methods, so that children can learn enthusiastically. The results of the development show an increase in religious understanding in children which has a positive impact on individuals, families, and society. However, challenges such as differences in children's characters require a special approach from teachers so that development runs effectively. With good management and effective communication between managers and teachers, TK/TPA development can create a young generation that is academically intelligent, has noble morals, and has a strong understanding of religion.